Geopolymerization of low-grade bauxite - Nikolić, Irena (Materiali in tehnologije, 2014)
In terms of quality, bauxite ore can be classified as high- or low-grade ore. High-grade bauxite ores are used for alumina extraction using the Bayer process, while low-grade bauxite ores have a limited application. In this paper we investigate the possibility of evaluating low-grade bauxite ores with the geopolymerization process. The influence of the synthesis parameters, i.e., alkali and silicate dosages and alkali cations (Na+ and K+) on the compressive strength of bauxite-based geopolymers is evaluated. The results show that an increase in the alkali dosage has a beneficial effect on the strength of bauxite-based geopolymers, while the strengthening of geopolymers by increasing the silicate dosage is limited by the viscosity of the geopolymer paste. Moreover, Na-geopolymers reach higher values of the compressive strength than K-geopolymers.
Keywords: geopolimerizacija; geopolymerization; bauxite; boksit; polymerization degree; stopnja polimerizacije; tlačna trdnost; compressive strength